2012
DOI: 10.1007/978-3-642-33996-7_18
|View full text |Cite
|
Sign up to set email alerts
|

Congestion Games with Capacitated Resources

Abstract: Abstract. The players of a congestion game interact by allocating bundles of resources from a common pool. This type of games leads to well studied models for analyzing strategic situations, including networks operated by uncoordinated selfish users. Congestion games constitute a subclass of potential games, meaning that a pure Nash equilibrium emerges from a myopic process where the players iteratively react by switching to a strategy that diminishes their individual cost. With the aim of covering more applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Recently, Biló and Vinci [5] studied a congestion game with a global priority classes that can contain multiple jobs and characterize the price of anarchy as a function of the number of classes. Gourvès et al [15] studied capacitated congestion games to characterize the existence of pure Nash equilibria and computation of an equilibrium when they exist. Piliouras et al [24] assumed that the priority lists are unknown to the players a priori and consider different risk attitudes towards having a uniform at random ordering.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, Biló and Vinci [5] studied a congestion game with a global priority classes that can contain multiple jobs and characterize the price of anarchy as a function of the number of classes. Gourvès et al [15] studied capacitated congestion games to characterize the existence of pure Nash equilibria and computation of an equilibrium when they exist. Piliouras et al [24] assumed that the priority lists are unknown to the players a priori and consider different risk attitudes towards having a uniform at random ordering.…”
Section: Related Workmentioning
confidence: 99%
“…Farzad et al [16] studied priority based selfish routing for non-atomic and atomic users and analyzed the inefficiency of equilibrium. Gourvès et al [19] studied capacitated congestion games to characterize the existence of pure Nash equilibria and computation of an equilibrium when they exist. Piliouras et al [29] assumed that the priority lists are unknown to the players a priori and consider different risk attitudes towards having a uniform at random ordering.…”
Section: Related Workmentioning
confidence: 99%
“…We analyze a potential function that is introduced by Gourvès et al [19]. Define the rank of job i ∈ N on machine j ∈ M by r(i, j) = |{i ∈ N | π j (i ) ≤ π j (i)}|.…”
Section: Proofmentioning
confidence: 99%
“…Rosenthal showed that pure Nash equilibria always exist for such games [13]. Weighted congestion games, with player-specific utility functions, were introduced by Milchtaich [14], and recently studied in several contexts [15][16][17][18][19]. In particular, a class of congestion games with capacitated resources, where each resource is associated with a capacity level, representing the maximum number of users that such a resource may simultaneously accommodate, was recently investigated in [19].…”
Section: Related Workmentioning
confidence: 99%